Service quality in Malaysian higher education: students’ perceptions and expectations / Noraini Yaumiddin. - Yaumiddin, Noraini (Universiti Teknologi MARA Cawangan Selangor, 2011)
This study examines the perceptions and expectations of undergraduate students concerning the quality of service at a private university in Malaysia. It was found that students were critical of many aspects of service, especially with regard to equipment, facilities and record keeping. Students were, however, relatively positive about the quality and the performance of their lecturers. The area that needed most improvement was the valuation placed by the university on feedback from students. It is suggested that further studies are needed to enable universities to compete in an increasingly competitive market-orientated industry.